Development of Canva-Based Interactive Learning Media on Business Opportunity Material in the Fashion Sector at Vocational School - Riska, Ria; Sintawati, Esin; Kulsum, Umi; Devi, Rentya Sari (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This project aims to develop interactive learning media using Canva that is effective, engaging, and suitable for teaching business potential in the fashion industry at public vocational schools. This study employs a research and development (R&D) methodology utilizing the ADDIE model for its design framework. This research was conducted at Public Vocational School 5 Malang. The research tool comprises a questionnaire. The study found that using the Canva application to create interactive learning media for the Basics of Electronics subject received a validation score of 91.76% from material experts I and II, which means it is considered very valid. Additionally, media experts I and II provided a validation average of 91.5%, also categorizing it as very valid. The practicality test yielded an average score of 95.40% across all dimensions, classifying it as highly practical. The validation and practicality findings of the interactive learning media utilizing the Canva application were deemed